Gestão de Transferência de Tecnologia na Inova Unicamp - Alexandre Aparecido Dias; Geciane Silveira Porto (RAC: Revista de Administração Contemporânea, 2013)
The aim of this study is to verify how Inova Unicamp manages its technology transfer (TT) process. A TT process can be understood as the passage of technology and knowledge from one organization to another (Bozeman, 2000). We conducted a qualitative study using a semi-structured interview of the institution directors. The results reveal that the TT Inova Unicamp model management is in a continuous maturing process, but must still overcome bottlenecks related to a shortage of permanent staff, a large number of temporary staff and a lack of an institutional policy to regulate the creation of spin-off companies.